PERAN SIKAP DALAM MEMEDIASI PENGARUH PENGETAHUAN TENTANG LINGKUNGAN TERHADAP NIAT MEMBELI PRODUK HIJAU PENDINGIN UDARA MEREK LG DI DENPASAR - Putri, Putu Tara Ayu Paramita; Sukaatmadja, I Putu Gde; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen, 2015)
The issue of the environment is now a public concern. Marketers today do green marketing by creating green products to attract consumers. The purpose of this study was to determine the role of environmental concern in mediating the effect of environmental knowledge on the purchase intention of green product in the electronics products LG brand air conditioners in the city of Denpasar. Sample size of 100 people, with a non-probability sampling method, especially incidental and purposive sampling using PLS analysis (Partial Least Square). The results of this study show the data analyzed environmental knowledge has a positive and significant effect either on the attitudes toward environmental and green purchase intention. Attitudes toward environmental has significant partially mediate the effect of environmental knowledge of the green purchase intention.
Keywords: green marketing, green product, environmental knowledge, attitudes toward environmental, green purchase intention.